Cultural Adaptation of Regional Postgraduate Students at Makassar State University: A Study of Social and Academic Interaction - Najamuddin; Ainun Mardiana; Alimin Alwi (International Journal of Education, Vocational and Social Science, 2025)
This study aims to analyze the factors that facilitate the cultural adaptation of out-of-town postgraduate students in terms of social and academic interactions at Makassar State University. Out-of-town students often face various challenges, such as cultural differences, more complex learning systems, and limitations in building social networks. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, observation, and documentation. The results of the study indicate that social support from peers, lecturers, and the campus community are the main factors that help students adjust to a new environment. Intercultural communication skills, participation in student organizations, and the use of technology, especially social media and online discussion groups, also contribute to accelerating the process of student adaptation. The main strategies implemented by students in adapting include building academic independence, developing communication skills, and utilizing digital resources to support the learning process and social interactions.